Spectroscopy of nanoscale crystalline structural elements; Вестник Карагандинского университета. Серия Физика; № 3 (99) - Borodin Yu. V. Yuri Viktorovich; Sysolov K. V. Konstantin Vladislavovich; Rande V. R. Valeriya Romanovna; Vavilova G. V. Galina Vasilievna; Stary O. Oldrikh (2020, 2020)
The study of structural elements, nanoparticles, microblocks and other nanoscale objects was an important part of the study of crystals non - equilibrium properties. The behavior of nanoscale structures allows us to judge the dynamics of the crystal lattice during doping, deformation, and interactions with radiation. Along with x - ray and electron microscopic studies, optical methods for determining the size of nanoscale objects, the energy of their electrons, and the symmetry of electronic States are increasingly being used. Among nanoscale objects, proton - separated structural elements (PSE) attract special attention in connection with the development of crystal structure block - hierarchical (BH) model. In this paper, we consider the possibility of calculating the size of PSE crystals in a model of quantum - dimensional structures. According to this model except values of the crystal potential in PSE, you should consider the area of high electron density, the existence of which is beyond the scope of conventional theory. Experimental data allow us to determine the position of this zone as localized around the atomic core of the PSE. Note that the atomic backbone generally coincides with the unit cell, that is, it consists of the same number of atoms and has the same point symmetry group.